Progression of scarring trachoma in Tanzanian children: A four-year cohort study. - Athumani M Ramadhani; Tamsyn Derrick; David Macleod; Patrick Massae; Elias Mafuru; Aiweda Malisa; Kelvin Mbuya; Chrissy H Roberts; William Makupa; Tara Mtuy; Robin L Bailey; David C W Mabey; et al. (Public Library of Science (PLoS), 2019)
Background Trachoma is a progressive blinding disease initiated by infection of the conjunctiva with Chlamydia trachomatis. Repeated infections are thought to cause chronic inflammation, which drives scarring, leading to in-turning of the eyelids. The relationship between C. trachomatis, clinical inflammation and scarring development in children is not fully understood due to a paucity of longitudinal studies with infection data at frequent follow-up. Methods and findings This longitudinal cohort study took place in northern Tanzania. Children aged 6-10 years at baseline were eligible for inclusion. Participants were visited every three months for four years. Clinical signs and conjunctival swabs for C. trachomatis detection by qPCR were collected at each time-point. Conjunctival photographs from baseline and final time-points were graded and compared side-by-side to determine scarring incidence and progression. Of the 666 children enrolled in the study, outcome data were obtained for 448. Scarring progression was detected in 103/448 (23%) children; 48 (11%) of which had incident scarring and 55 (12%) had progression of existing scarring. Scarring was strongly associated with increasing episodes of trachomatous papillary inflammation (TP). Weaker associations were found between episodes of C. trachomatis infection and follicular trachoma (TF) with scarring progression in unadjusted models, which were absent in multivariable analysis after adjusting for inflammation (multivariable results: C. trachomatis p = 0.44, TF p = 0.25, TP p = <0.0001, age p = 0.13, female sex p = 0.05). Individuals having TP at 30% or more of the time-points they were seen had an odds ratio of 7.5 (95%CI = 2.7-20.8) for scarring progression relative to individuals without any TP detected during the study period. Conclusions These data suggest that the effect of infection on scarring progression is mediated through papillary inflammation, and that other factors contributing to the development of inflammation, in addition to C. trachomatis infection, may be important in driving conjunctival scarring progression in children. The addition of TP as a measure in trachoma control programs would provide an indication of the future risk of developing scarring sequelae.